The Relationship Between Some Physical Abilities and Handball Goalkeepers Speed of Motor Response - Shehab, Huda; Abed, Raghda (Journal of Physical Education, 2017)
The aim of the research is to identify the values of some motor abilities and response speed in handball goalkeepers as well as identifying the relationship between some motor abilities and response speed in handball goalkeepers. The researchers hypothesized no significant relationship between some motor abilities and speed of motor response. The researcher used the descriptive method. The subjects were handball goalkeepers aged 15 – 17 years old. The researcher applied many tests to measure motor response speed in goalkeepers, the data was collected and treated using proper statistical operations. The researcher concluded that handball goalkeeper’s motor response speed is positively affected by some motor abilities like agility, coordination and flexibility